2023
DOI: 10.1177/08850666231185752
|View full text |Cite
|
Sign up to set email alerts
|

Everything About Pulse Oximetry—Part 1: History, Principles, Advantages, Limitations, Inaccuracies, Cost Analysis, the Level of Knowledge About Pulse Oximeter Among Clinicians, and Pulse Oximetry Versus Tissue Oximetry

Abstract: Purpose: Pulse oximetry is a noninvasive medical technique that measures the amount of oxygen in a person’s blood by shining light through their skin. It is widely used in medical care and is considered as important as the 4 traditional vital signs. In this article, it was aimed to review all aspects of pulse oximetry in detail. Materials and Methods: The international and national reliable sources were used in the literature review for critical data analysis. A total of 13 articles including 9 reviews, 1 comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Portable pulse oximeters have been shown to be accurate in preoperative patients who do not have any cardiovascular compromise. Tekin K et al concluded that portable pulse have significant impact on patient care in modern medicine and can reliably be used to detect hypoxemia 11 . Smith RN compared oxygen saturation levels obtained from portable and conventional intensive care unit monitors for patients who were scheduled to undergo elective and emergency procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Portable pulse oximeters have been shown to be accurate in preoperative patients who do not have any cardiovascular compromise. Tekin K et al concluded that portable pulse have significant impact on patient care in modern medicine and can reliably be used to detect hypoxemia 11 . Smith RN compared oxygen saturation levels obtained from portable and conventional intensive care unit monitors for patients who were scheduled to undergo elective and emergency procedures.…”
Section: Discussionmentioning
confidence: 99%